Migration in the Swiss Alps and Swiss Jura from the Middle Ages to the mid-20th century: a brief review - Anne-Lise Head-König (Revue de Géographie Alpine)
This paper aims at retracing the important phases of migrations in the alpine regions and the Jura from the Middle Ages up to the middle of the 20th century. Migration has always functioned as a necessary complement to the resources of the inhabitants of the upland regions and it increases when the economic disparity with the lowlands becomes more marked. A striking characteristic of such migration is the great diversity that can be observed, since not only the destinations of the migrants varied from community to community, but also different forms of mobility coexisted within the same territory. Migration might be seasonal, pluriannual, lifelong or even definitive. It is also notable that the various types of migration can be observed to be part of a plurisecular tradition, apart from some significant exceptions, such as the emigration of the Walser, enforced migrations and the new types of migration as from the second half of the nineteenth century. The mobility of part of the population was also a consequence of modifications deriving from changes in the prevalent type of production (animal husbandry instead of the cultivation of cereals), as well as from demographic factors. In addition to these factors one can observe the role played by political institutions throughout the period under study: seigneurial power in the Middle Ages, the communal and cantonal instances until the second half of the nineteenth century, and afterwards the federal authorities.